2010
DOI: 10.1007/s10140-009-0854-2
|View full text |Cite
|
Sign up to set email alerts
|

Intraobserver and interobserver agreement of the interpretation of pediatric chest radiographs

Abstract: The objective of this study is to quantify the magnitude of intraobserver and interobserver agreement among physicians for the interpretation of pneumonia on pediatric chest radiographs. Chest radiographs that produced discordant interpretations between the emergency physician and the radiologist's final interpretation were identified for patients aged 1-4 years. From 24 radiographs, eight were randomly selected as study radiographs, and 16 were diversion films. Study participants included two pediatric radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
55
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 19 publications
7
55
0
2
Order By: Relevance
“…Of course, variability in interpretation can also be influenced by other factors than training or experience, such as radiographic quality, and individual radiologist variability (TUDOR; FINLAY; TAUB, 1997;HERMAN et al, 1975;KLINE, 2010). Even amongst experienced and trained radiologists, there is variation in interpretation and diagnostic performance, as we observed and as has been reported (BREALEY; SCALLY; THOMAS, 2002).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Of course, variability in interpretation can also be influenced by other factors than training or experience, such as radiographic quality, and individual radiologist variability (TUDOR; FINLAY; TAUB, 1997;HERMAN et al, 1975;KLINE, 2010). Even amongst experienced and trained radiologists, there is variation in interpretation and diagnostic performance, as we observed and as has been reported (BREALEY; SCALLY; THOMAS, 2002).…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, it is possible that some discrepancies will be associated to simple human error related to cognitive bias (GUNDERMAN, 2009), different emotions or physical tiredness during the interpretation (TUDOR; FINLAY; TAUB, 1997;HERMAN et al, 1975;KLINE, 2010). This can happen to any observers independent of the degree of training and experience.…”
Section: Discussionmentioning
confidence: 99%
“…Few prior studies have assessed the reliability of chest radiograph findings in children. 3,5,12,14,15 We found a high degree of agreement among radiologists for radiologic findings consistent with bacterial pneumonia when standardized interpretation criteria were applied. In this study, we identified radiographic features of pneumonia, such as alveolar infiltrate and pleural effusion, that were consistently identified by different radiologists reviewing the same radiograph and by the same radiologist reviewing the same radiograph.…”
Section: Discussionmentioning
confidence: 73%
“…2,3,15,18 Many of these prior studies emphasized variation in detection of radiographic findings that would not typically alter clinical management. We observed high intra-rater, and inter-rater reliability among radiologists for the findings of alveolar infiltrate and pleural effusion.…”
Section: Discussionmentioning
confidence: 99%
“…Even between 54 and 57 days of gestation (Group II) there is a 30% estimated error rate in estimated fetal number. This is due to a combination of factors and may be compounded by human cognitive bias errors (GUNDERMAN, 2009), the mental or physical fatigue of the radiologist, and observer variability (JOHNSON; KLINE, 2010;TUDOR et al, 2007). These factors may be independent of the training and experience of the radiologist.…”
Section: Discussionmentioning
confidence: 99%